UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH MELALUI BEA PERALIHAN HAK ATAS TANAH DAN BANGUNAN DI KABUPATEN BOJONEGORO - Edy Suhartono; Zafira MP (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2018)
Regional Original Income (PAD) can be seen as one of the indicators or criteria for measuring a region's dependence on the central government in carrying out development. Therefore, the government continues to strive to implement regional tax revenues to increase regional original income in tax collection. Regional Original Income (PAD) can be used as a determination of the degree of independence of an area. In order for BPHTB collection to work properly, the Regional Government concerned must first have a Regional Regulation (Perda) which regulates it, if it does not have a Regional Regulation, then the Regional Government may not collect BPHTB. Thus, people who buy property in regions that do not have a local regulation, the community does not need to pay the BPHTB tax. The community also needs to be aware that in the future there will be a diversity of systems and patterns of BPHTB collection wherein each local government is given the freedom to manage according to their capabilities.